In vitro activation of natural killer-like cytotoxicity by specifically in vivo primed T-helper lymphocytes in the rat. - Britten, V (1984)
The interaction between the rat non-cytotoxic T lymphocyte subset, which is marked by the W3/25 monoclonal antibody, and natural killer cells was investigated. Specifically in vivo primed lymph node cells were restimulated in vitro with the priming antigen and co-cultured with a source of natural killer cells and their precursors. Cytotoxic activity, generated during a 4 day incubation period, was assessed by lysis of a rat natural killer cell-sensitive tumour target cell line, y3Ag123. This cytotoxic activity was more fully described as natural killer cell cytotoxicity on the basis of target cell specificity, using a range of natural killer cell-susceptible and -resistant targets. The W3/25-positive T cell, separated from the in vivo primed lymph node cells by nylon wool column elution, antibody labelling and sorting on the fluorescence-activated cell sorter, was shown to be necessary to stimulate the generation of this activity. W3/25-negative cells were not active in this respect. The activation was shown to be mediated via lymphokine(s), probably interleukin-2, present in concanavalin A-induced lymphocyte culture supernatants. These supernatants could be used to substitute for in vivo primed, restimulated W3/25-positive lymph node cells in activating natural killer cell cytotoxicity from normal spleen cells. Nylon wool column-eluted spleen cells, activated in vitro with conditioned medium were separated into OX8-positive and OX8-negative subsets using the fluorescence-activated cell sorter. The distribution of cytotoxic activity related to that of freshly derived rat natural killer cells.